SPARC is required for the maintenance of glucose homeostasis and insulin secretion in mice. (30th January 2019) - Atorrasagasti, Catalina; Onorato, Agostina; Gimeno, María L.; Andreone, Luz; Garcia, Mariana; Malvicini, Mariana; Fiore, Esteban; Bayo, Juan; Perone, Marcelo J.; Mazzolini, Guillermo D.
Abstract : Obesity, metabolic syndrome, and type 2 diabetes, three strongly interrelated diseases, are associated to increased morbidity and mortality worldwide. The pathogenesis of obesity-associated disorders is still under study. Secreted protein acidic and rich in cysteine (SPARC) is a matricellular glycoprotein expressed in many cell types including adipocytes, parenchymal, and non-parenchymal hepatic cells and pancreatic cells. Studies have demonstrated that SPARC inhibits adipogenesis and promotes insulin resistance; in addition, circulating SPARC levels were positively correlated with body mass index in obese individuals. Therefore, SPARC is being proposed as a key factor in the pathogenesis of obesity-associated disorders. The aim of this study is to elucidate the role of SPARC in glucose homeostasis. We show here that SPARC null (SPARC −/− ) mice displayed an abnormal insulin-regulated glucose metabolism. SPARC −/− mice presented an increased adipose tissue deposition and an impaired glucose homeostasis as animals aged. In addition, the absence of SPARC worsens high-fat diet-induced diabetes in mice. Interestingly, although SPARC −/− mice on high-fat diet were sensitive to insulin they showed an impaired insulin secretion capacity. Of note, the expression of glucose transporter 2 in islets of SPARC −/− mice was dramatically reduced. The present study provides the first evidence that deleted SPARC expression causes diabetes in mice. Thus, SPARC deficient mice constitute a valuable model for studies concerning obesity and its related metabolic complications, including diabetes.